2009
DOI: 10.1097/eja.0b013e328318c5b6
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of distal ulnar nerve anatomy using ultrasound in volunteers to identify an optimum approach for neural blockade

Abstract: Our study demonstrates that ultrasound can be utilized to identify the ulnar nerve and artery in the forearm. This implies that traditional landmarks will not be required prior to neural blockade. We have suggested a point for blockade of the nerve to reduce risk of vascular puncture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Approximately the junction of the middle and proximal third of the forearm, proximal to the divergence from the ulnar artery. 7 The arm was abducted and externally rotated with the palm facing up. Needle advancement was in-plane anterior to posterior.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately the junction of the middle and proximal third of the forearm, proximal to the divergence from the ulnar artery. 7 The arm was abducted and externally rotated with the palm facing up. Needle advancement was in-plane anterior to posterior.…”
Section: Methodsmentioning
confidence: 99%
“…did not find a difference in patient satisfaction, whereas Lam et al [1] found a statistically significant difference in their study. The maintenance of motor function is an important advantage of distal nerve blocks because of the need to protect the arm operated on from inadvertent injury [10].…”
Section: Discussionmentioning
confidence: 99%
“…A long axis slide was used to trace the median nerve distally to 5 cm from the proximal wrist crease [10]. A short axis slide was then performed medially to locate the ulnar artery and the ulnar nerve adjacent to it [12]. Upon location of these structures, 1.5 mL of 0.5% lidocaine with 5 mcg/mL epinephrine was injected subcutaneously at the medial border of the ultrasound probe.…”
Section: Methodsmentioning
confidence: 99%